Do people with low back pain walk differently? A systematic review and meta-analysis - Jo Armour Smith; Heidi Stabbert; Jennifer J. Bagwell; Hsiang-Ling Teng; Vernie Wade; Szu-Ping Lee (Elsevier, 2022)
Background: The biomechanics of the trunk and lower limbs during walking and running gait are frequently assessed in individuals with low back pain (LBP). Despite substantial research, it is still unclear whether consistent and generalizable changes in walking or running gait occur in association with LBP. The purpose of this systematic review was to identify whether there are differences in biomechanics during walking and running gait in individuals with acute and persistent LBP compared with back-healthy controls. Methods: A search was conducted in PubMed, CINAHL, SPORTDiscus, and PsycINFO in June 2019 and was repeated in December 2020. Studies were included if they reported biomechanical characteristics of individuals with and without LBP during steady-state or perturbed walking and running. Biomechanical data included spatiotemporal, kinematic, kinetic, and electromyography variables. The reporting quality and potential for bias of each study was assessed. Data were pooled where possible to compare the standardized mean differences (SMD) between back pain and back-healthy control groups. Results: Ninety-seven studies were included and reviewed. Two studies investigated acute pain and the rest investigated persistent pain. Nine studies investigated running gait. Of the studies, 20% had high reporting quality/low risk of bias. In comparison with back-healthy controls, individuals with persistent LBP walked slower (SMD = -0.59, 95% confidence interval (95%CI): -0.77 to -0.42)) and with shorter stride length (SMD = -0.38, 95%CI: -0.60 to -0.16). There were no differences in the amplitude of motion in the thoracic or lumbar spine, pelvis, or hips in individuals with LBP. During walking, coordination of motion between the thorax and the lumbar spine/pelvis was significantly more in-phase in the persistent LBP groups (SMD = -0.60, 95%CI: -0.90 to -0.30), and individuals with persistent LBP exhibited greater amplitude of activation in the paraspinal muscles (SMD = 0.52, 95%CI: 0.23-0.80). There were no consistent differences in running biomechanics between groups. Conclusion: There is moderate-to-strong evidence that individuals with persistent LBP demonstrate differences in walking gait compared to back-healthy controls.